1999
DOI: 10.1038/sj.bjc.6690377
|View full text |Cite
|
Sign up to set email alerts
|

Haematogenous cytokeratin 20 mRNA as a predictive marker for recurrence in oral cancer patients

Abstract: We examined the expression of cytokeratin 20 (CK20) mRNA in the peripheral blood of oral squamous cell carcinoma (SCC) patients by reverse transcriptase polymerase chain reaction (RT-PCR). Eleven out of 12 oral SCC patients showed positive RT-PCR results. However, there is no clear relationship between the haematogenous CK20 mRNA and the metastasis. After initial treatment, all of the tumour-free survivors tested showed negative RT-PCR results. CK20 mRNA in peripheral blood can be used as a marker for tumour r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…1 We also noted that cancer cells in the peripheral blood of patients with oral SCC were frequently detected by RT-PCR for cytokeratin 20 mRNA, and that there was no clear relationship between the hematogenous cancer cells and the metastasis. 2 Furthermore, by microdissection zymography, we demonstrated that active MMP2 in cancer cell nests could be a predictive marker for metastasis formation in patients with oral SCC. 3 The precise molecular mechanisms of invasion and metastasis of oral cancer, however, especially the interaction between cancer cells and host cells, are still unknown.…”
mentioning
confidence: 84%
“…1 We also noted that cancer cells in the peripheral blood of patients with oral SCC were frequently detected by RT-PCR for cytokeratin 20 mRNA, and that there was no clear relationship between the hematogenous cancer cells and the metastasis. 2 Furthermore, by microdissection zymography, we demonstrated that active MMP2 in cancer cell nests could be a predictive marker for metastasis formation in patients with oral SCC. 3 The precise molecular mechanisms of invasion and metastasis of oral cancer, however, especially the interaction between cancer cells and host cells, are still unknown.…”
mentioning
confidence: 84%
“…Previous studies using such markers in HNSCC have suggested a low specificity (Kawamata et al, 1999;Hamakawa et al, 2000a), particularly because of false-positive results associated with benign epithelial rests in lymph nodes found in 1.6% of cervical nodes, but only in lymph nodes from level I (Gnepp, 2000;Hamakawa et al, 2000b). The assay used in the present study, that is, RT -PCR detection of CK19 mRNA, has been developed in our laboratory for the detection of occult carcinomatous cells in mediastinal lymph nodes in non-small-cell lung carcinoma (Saintigny et al, 2005) and by other teams in various carcinomas (Van Trappen et al, 2001;Inokuchi et al, 2003;Favia et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these molecular studies performed in HNSCC have been suspected to have a low specificity (Kawamata et al, 1999;Hamakawa et al, 2000a). We therefore decided to design a method based on a realtime Taqman PCR reverse -transcriptase polymerase chain reaction (real-time RT -PCR) assay to detect cytokeratin 19 (CK19) mRNA marker of occult tumour cells in lymph nodes of patients undergoing neck dissection for HNSCC as such a marker has been shown to detect accurately micrometastases in patients with lung, oesophageal, gastric, breast or colorectal carcinoma (Izbicki et al, 1997;Czerniecki et al, 1999;Weitz et al, 1999;Gai et al, 2000;Saintigny et al, 2005).…”
mentioning
confidence: 99%
“…The overall survival rate has remained unchanged in recent years, despite extensive research on the biological and molecular aspects of HNSCC (2)(3)(4)(5)(6)(7)(8)(9). Although most HNSCC is etiologically linked with smoking and/or alcohol drinking or betel chewing, clearly there are patients who develop HNSCC despite the absence of exposure to these agents, and in the absence of any obvious predisposing genetic defect (10).…”
Section: Introductionmentioning
confidence: 99%